inggris - Gunsu Nurmansyah (Faculty of Law-Universitas Bandar Lampung, 2024)
The independence of judicial power is an absolute requirement for law enforcement and justice. The independence of judges is an essential principle in a democratic legal system. Judges should be free from political influence or pressure from any party and only decide cases based on relevant facts and laws. The question is, what is the role of judges in maintaining the independence of the judiciary, and what is the legal basis for guaranteeing judicial power to realize freedom and justice for the community in the judiciary in Indonesia? The role of judges in maintaining judicial independence is urgent in ensuring justice and truth in a case. Judges must have high integrity and not be pressured by any party, including the government or specific interest groups. Judicial independence also means that judges should be free to make decisions without interference from other parties. The legal basis for guaranteeing judicial power to realize freedom and justice is an essential principle in Indonesia's legal system. This principle emphasizes that the court must be free from political interference or pressure from any party to carry out its duties fairly and objectively.